Design & Simulation of Flexible Control For 3-phase Grid Connected Solar PV System - Srinivasan, R.; R.Balamurugan, C.; Shanmugasundaram, N. (International Journal of Engineering and Technology, 2018)
A non-linear control progression for 3-stage (phase) lattice (grid) associated of PV generator is proposed here. This system is designed with PV arrays; grid filter; a voltage source inverter and a stimulating lattice or network. The regulator purposes are classified into three sections: i) making sure that the Most power point tracking (MPPT) are having photovoltaic boards, ii) assuringÂ  for power or control factor entity or unit in the grid plane iii) ensuring large-scale asymptotic constancy of the closed loop system. Lyapunov modelling approach is used by the controller and carried out by considering nonlinear model of the integral method. It is formally shown that the projected system controller congregates the scope of the objectives using a hypothetical constancy with stability analysis as well as simulation results.Â Â